AN ASSESSMENT OF THE SOCIAL AND POLITICAL FUNCTION OF THE INTELLECTUAL - Ülkü Ayşe OĞUZHAN BÖREKCİ (International Journal of Eurasia Social Sciences, 2017)
Throughout history, in each society, there have been prominent people with their "intellectual/luminary" identities. Along with various approaches regarding the emergence of the intellectual as a social and political actor and their role in this respect, there has been a consensus that they are also a product of the modern Western society. Hence, with the impact of the Renaissance, the new conditions appeared in the West created a new type of individual. This new type, which is the first example of the modern intellectual, fought against the ideology that the church tried to disseminate since the 15th century. In this respect, the mind, the logic and the intelligence of the intellectual individual came into prominence. The idea of the Enlightenment was at the core of the thought system of the intellectual; and it was agreed that anything that could not be researched, questioned and criticised could not be accepted. Since the 19th century, the critical identity of the modern intellectual has been a strategic and valuable asset. In addition to this, parallel to social, historical, political and scientific developments, the intellectual has evolved, and various meanings have been attributed to how their social – political function should be. In this study, an assessment on the concept of the intellectual, its attributes, the evolution it went through, and its social-political functions has been carried out. While this assessment is conducted, what kind of an intellectual is portrayed in both "modern" and "modernising" societies is discussed. In the end, a variety of deductions have been made as to how the attributes of an intellectual should be in the normative sense.